2017
DOI: 10.1111/2041-210x.12723
|View full text |Cite
|
Sign up to set email alerts
|

Using joint species distribution models for evaluating how species‐to‐species associations depend on the environmental context

Abstract: Summary Joint species distribution models (JSDM) are increasingly used to analyse community ecology data. Recent progress with JSDMs has provided ecologists with new tools for estimating species associations (residual co‐occurrence patterns after accounting for environmental niches) from large data sets, as well as for increasing the predictive power of species distribution models (SDMs) by accounting for such associations. Yet, one critical limitation of JSDMs developed thus far is that they assume constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
144
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(147 citation statements)
references
References 49 publications
(73 reference statements)
1
144
2
Order By: Relevance
“…This particular result contradicts our initial hypothesis that the joint model would improve predictive performance, as similar studies have found that joint models generally improve the quality of fit and predictive performance (relative to individual models) for various communities (Clark et al, ; Harris, ; Ovaskainen, Abrego, et al, ; Taylor‐Rodríguez et al, ; Tikhonov et al, ). For example, Clark et al () and Taylor‐Rodríguez et al () show that joint models of forest communities improve predictive performance and the prediction of species richness over equivalent individual models (Guisan & Rahbek, ), with a similar study of plant communities confirming these findings (e.g.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…This particular result contradicts our initial hypothesis that the joint model would improve predictive performance, as similar studies have found that joint models generally improve the quality of fit and predictive performance (relative to individual models) for various communities (Clark et al, ; Harris, ; Ovaskainen, Abrego, et al, ; Taylor‐Rodríguez et al, ; Tikhonov et al, ). For example, Clark et al () and Taylor‐Rodríguez et al () show that joint models of forest communities improve predictive performance and the prediction of species richness over equivalent individual models (Guisan & Rahbek, ), with a similar study of plant communities confirming these findings (e.g.…”
Section: Discussioncontrasting
confidence: 76%
“…For example, Clark et al () and Taylor‐Rodríguez et al () show that joint models of forest communities improve predictive performance and the prediction of species richness over equivalent individual models (Guisan & Rahbek, ), with a similar study of plant communities confirming these findings (e.g. Tikhonov et al, ). Studies applying joint models to freshwater communities suggest that shared responses to environmental conditions may be more important in determining community composition than residual correlations between taxa (Inoue, Stoeckl, & Geist, ; Pollock et al, ; Royan et al, ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The different approaches might partially contribute to the divergence from our results, which suggested that sample sizes had minor influence on model predictability. Many studies have demonstrated that JSDMs consistently over-perform single-species SDMs implemented by GLMs (Hui et al 2013, Tikhonov et al 2017, Clark et al 2017, boosted regression trees, neutral network (Harris 2015), and spatial delta models (Thorson and Barnett 2017). As the marginal predictions usually involve extensive averaging among simulations, the predicted values tend to be stable (small standard error in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4, 5 and 6) but less precise for site-specific predictions. In addition, most JSDMs assume constant species associations over environmental gradients, space and time (Warton et al 2015a; but see Tikhonov et al 2017), which is not likely to be true due to adaptive behaviors of organisms. JSDMs are powerful tools for analyzing the structure and assembly processes of biotic communities.…”
Section: Discussionmentioning
confidence: 99%